1997
DOI: 10.1021/cm970241e
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Modified MCM-48 Mesoporous Molecular Sieves

Abstract: MCM-48 mesoporous molecular sieves containing iron(III) were obtained using a direct sol−gel route followed by removal of the cetyltrimethylammonium hydroxide template before calcination. UV−visible, ESR, and XANES spectroscopies show that iron mostly occupies tetrahedral sites of the siliceous walls. The formation of oxide nanoclusters in the channels is favored in the presence of the organic template molecules during calcination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 23 publications
4
46
1
Order By: Relevance
“…All samples exhibit a peak around 260 nm. This band is assigned to the charge transfer between the Fe 3+ and O 2-atoms in the framework of Fe-O-Si, indicating isolated, tetrahedrally-coordinated Fe species [19]. In addition to this peak, a shoulder appeared at around 330 nm in the Fe-2 sample which would be consistent with the presence of polyferrate (Fe-O-Fe) n in the framework.…”
Section: Catalytic Testsmentioning
confidence: 69%
“…All samples exhibit a peak around 260 nm. This band is assigned to the charge transfer between the Fe 3+ and O 2-atoms in the framework of Fe-O-Si, indicating isolated, tetrahedrally-coordinated Fe species [19]. In addition to this peak, a shoulder appeared at around 330 nm in the Fe-2 sample which would be consistent with the presence of polyferrate (Fe-O-Fe) n in the framework.…”
Section: Catalytic Testsmentioning
confidence: 69%
“…Silicalite-I has no bands in the 200-700 nm region, while Fe-ZSM-5 shows a strong absorption band centered at 240-250 nm. The band at 240-250 nm may be assigned to the dπ-pπ charge-transfer transition between the iron and oxygen atoms in the framework of Fe-O-Si in zeolite (19,20). Similar phenomena have been observed in Ti-O-Si species of TS-1 (10,21,22).…”
Section: Fig 2 Uv Raman Spectra Of (A) Silicalite-imentioning
confidence: 99%
“…Notably, many efforts have been devoted to the incorporation of Al, Ti and V into SBA-15 [11][12][13][14][15][16][17], including the two-steps pH adjusting methods [14,15], the hydrolysis-controlled methods [15,16], and microwave-hydrothermal procedures [17]. However, the incorporation of Fe into the framework of SBA-15 by simple direct hydrothermal methods prepared in acidic media has rarely been reported [18], although Fe-zeolites and Fe-MCM-41 prepared in basic media have been widely investigated [6,[19][20][21][22][23][24][25]. It has been reported that Fe species in the framework of mesoporous materials such as MCM-41 [23], MCM-48 [24], and HMS [25] are tetrahedral coordinated but easily escape from the framework and turn to iron oxide when these materials are calcined at high temperature to remove the organic template.…”
Section: Introductionmentioning
confidence: 99%
“…However, the incorporation of Fe into the framework of SBA-15 by simple direct hydrothermal methods prepared in acidic media has rarely been reported [18], although Fe-zeolites and Fe-MCM-41 prepared in basic media have been widely investigated [6,[19][20][21][22][23][24][25]. It has been reported that Fe species in the framework of mesoporous materials such as MCM-41 [23], MCM-48 [24], and HMS [25] are tetrahedral coordinated but easily escape from the framework and turn to iron oxide when these materials are calcined at high temperature to remove the organic template. Metal ions are generally in an isolated state in acidic solution, whereas they easily precipitate from solution to form metal oxides in basic solution.…”
Section: Introductionmentioning
confidence: 99%